Goodbye Old Man? The Evolution of the Soldier–Horse Relationship in Myth and Memory, 1880–1939. - Flynn, Jane (Humanimalia, 2024)
In the Great War’s immediate aftermath, many images of the soldier and his horse that had been popular during the War endured because they were still able to provide comfort. However, by the 1930s, the war horse was increasingly becoming, not a fact of military life, but a relic of its past. The War’s culmination had already proved to be a turning point in how the British public saw itself in relation to the soldier’s horse. Portrayals that had once been countered by reality now also started to gain a life of their own. Increasingly, the “real” became the imagined and the imagined became evidence that the events depicted had been “real”. It was not that the events recounted in images made popular during the War, such as Fortunino Matania’s Goodbye Old Man had never happened, but rather that what remained was becoming increasingly detached from the War as it had actually been fought.